Implementasi Perancangan Aplikasi Donasi Online Untuk Kegiatan Jumat Berkah Menggunakan Metode Model View Controller Berbasis Web (Studi Kasus: Organisasi Sulit Air Sepakat) - Wanda Octavia Eliza; Fitri Yanti (OKTAL : Jurnal Ilmu Komputer dan Sains, 2025)
This study aims to implement the design of an online donation application based on a website for the Jumat Berkah activity using the Model View Controller (MVC) method. The Sulit Air Sepakat (SAS) organization often faces obstacles in managing donations manually, which limits transparency and efficiency. By applying MVC, the system is structured through the separation of Model, View, and Controller components. The application was developed using PHP, PostgreSQL/MySQL, and integrated with Midtrans as a payment gateway. The testing methods applied were black box and white box testing. The results show that the application simplifies donation management, improves transparency, and provides real-time access for donors and administrators. This system supports SAS social activities to be more effective, accountable, and participatory.